Analisis Kepuasan Donatur Infak.In pada LAZNAS LMI - Ali Hamdan; Saifuddin Saifuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze donor satisfaction with the Infak.in donation platform. On the digital platform owned by LAZNAS LMI, identify the most superior service aspects and determine the areas that need to be evaluated for future platform development. The research method uses a quantitative approach, with primary data collected via an online questionnaire distributed to Infak.in donors. From a total of 2,500 donor records, a sample of 65 respondents was selected using the Slovin formula, with a confidence level of 88%. Data analysis techniques used include Customer Effort Score (CES), Customer Satisfaction Index (CSI), Net Promoter Score (NPS), and Top Box Analysis. The results showed that Infak.In's CES score was 3.4, which is in the intermediate category, indicating that there are still minor obstacles to the platform's ease of use. The CSI score reached 89%, which is in the very satisfied category, indicating that, in general, Infak.in's services have met donor expectations. Meanwhile, the NPS score of 42% falls into the 'great' category, indicating strong donor loyalty and a strong willingness to recommend the platform to others. The services most appreciated by donors are distribution reports and e-receipts, while the most popular programs are humanitarian and Palestinian programs. This study recommends improving ease of use, optimizing notifications, and expanding the platform's functionality.